2015
DOI: 10.1039/c5ra01754h
|View full text |Cite
|
Sign up to set email alerts
|

Natural and semisynthetic protein tyrosine phosphatase 1B (PTP1B) inhibitors as anti-diabetic agents

Abstract: Diabetes mellitus, which includes both type 1 and type 2 diabetes mellitus (T2DM), is a major disease that threatens human health worldwide. Protein tyrosine phosphatase 1B (PTP1B) is a promising molecularlevel therapeutic target that is effective in the management of T2DM. Natural products with various skeletons and diverse bioactivities offer opportunities for the development of new drugs and lead compounds with potent inhibitory activity against PTP1B in vitro and in vivo. Recently, a number of potent PTP1B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 94 publications
0
38
1
2
Order By: Relevance
“…The extract remarkably inhibited the activity of PTP1B with an IC 50 value in the range of 322-378 µg/mL (Figure 1). This activity is lower than the reported values for a variety of vegetables [22] and seaweed [23].…”
Section: Citationcontrasting
confidence: 48%
“…The extract remarkably inhibited the activity of PTP1B with an IC 50 value in the range of 322-378 µg/mL (Figure 1). This activity is lower than the reported values for a variety of vegetables [22] and seaweed [23].…”
Section: Citationcontrasting
confidence: 48%
“…Diabetes mellitus is a chronic disease that is triggered by insulin resistance or deficiency. This disease is one of the major risks to human well-being worldwide [105]. Long-term use of oral hypoglycaemic agents may reduce their pharmacological activity.…”
Section: Anti-diabetesmentioning
confidence: 99%
“…Diabetes mellitus (DM) a chronic metabolic disorder has become one of the world's most serious health concerns. Clinically, there are four types of DM, and type 2 diabetes mellitus (T2DM) is the most common form that causes many severe secondary complications, such as atherosclerosis, renal dysfunction and failure, cardiac abnormalities and ocular disorders (Rengasamy et al 2013;Wang et al 2015;Guo et al 2015). Shin's study showed that CGA (1) (10 and 20 mg kg -1 , intraperitoneal injection) effectively preserved the expression of tight junction protein and attenuated STZ-induced diabetic retinopathy in mice (Shin et al 2013).…”
Section: Hypoglycemic Activitymentioning
confidence: 99%